The Latino health experience: Past and future - Noreen Goldman; Anne R. Pebley (Proceedings of the National Academy of Sciences, 2026)
Latinos, a diverse group comprised primarily of immigrants and their descendants, are a large and growing part of the US population. Using our research from the past twenty years, we explore health outcomes and patterns among Latinos, many of which are distinct from those of other racial and ethnic groups. We contrast Latinos’ relatively high life expectancy during most of the past few decades with many ongoing health-related disadvantages including numerous chronic diseases and health conditions, disability and functional limitations, and survival during the COVID-19 pandemic. Our finding of a relatively weak social gradient in several health outcomes for Latinos suggests that being of higher socioeconomic status confers a smaller health benefit compared to being of lower status relative to the White population. We underscore the importance of occupational stratification and continued social and economic inequalities that underlie these health concerns. We use these findings to update our earlier speculation regarding future threats to the Latino mortality advantage to take into account the potential impact on health of current immigration policies and increasing risk from emerging and reemerging pathogens. The detrimental consequences of worsening Latino health could extend well beyond the Latino population, given its vital role in the US economy.